Opportunities and Challenges of Integrating Artificial Intelligence (AI) into Religious Education Systems: A Descriptive Study on Madrasa Education in Sri Lanka - Dr. H.L.M. Mohideen (RADINKA JAYA UTAMA PUBLISHER, 2025)
Madrasa education in Sri Lanka has historically served as a basis of Islamic learning and community development, providing instruction in Qur’an, Hadith, Fiqh, Arabic, and related disciplines, while also promoting moral and spiritual formation. In recent decades, some Madrasas have incorporated secular subjects, yet they continue to face challenges such as limited resources, traditional teaching methods, and the need to balance religious authenticity with modern relevance. Simultaneously, Artificial Intelligence (AI) is transforming global education through tools such as adaptive learning platforms, intelligent tutoring systems, natural language processing, and learning analytics, which enhance personalized learning, assessment, and administrative efficiency. This study explores the integration of AI in Madrasa education in Sri Lanka, examining potential opportunities, challenges, and lessons from global experiences. Using a qualitative methodology, data were collected from primary sources through observation and discussion with teachers, administrators, and students, alongside secondary sources including scholarly literature and policy documents. Findings indicate that AI can support personalized and adaptive learning, multilingual assistance, digital Qur’an and Hadith study aids, performance tracking, and resource management. However, technological limitations, financial constraints, cultural and religious concerns, and regulatory gaps present significant obstacles. The study concludes that careful, context-sensitive integration of AI can enhance pedagogical effectiveness, administrative efficiency, and global connectivity while preserving Islamic values. Future efforts should focus on localized AI tools, teacher training, and policy frameworks to ensure sustainable and culturally appropriate adoption.